Собственные колебания анизотропной полупроводниковой пластины в волноводе с поперечным магнитным полем - Шматько, А. А.; Мизерник, В. Н.; Одаренко, Е. Н. (Weber Co., 2015)
The new method of an analytical solution of a problem on semiconductor resonator eigenmodes in a waveguide on the basis of an Cauchy integral and interpolation Lagrange formula for arbitrary sizes of the resonator and permittivity tensor parameters of medium is offered. The analysis of the dispersion equation is performed and relations between problem parameters are established for three types of solutions: the localized modes, surface modes, modes with complex frequencies.
Keywords: полупроводниковая плазма; собственные колебания; волновод; интеграл Коши